Curriculum Innovation in Counselor Education: A Systematic Literature Review to Address the Demands of Modern Counseling Services: Inovasi Kurikulum dalam Pendidikan Konselor: Tinjauan Pustaka Sistematis untuk Memenuhi Tuntutan Layanan Konseling Modern - Putri Anditasari; Popy Mayasari Afendy; Elza Sabillah (Edukasi: Journal of Educational Research, 2026)
This study examines the direction and characteristics of curriculum innovation in counselor education, identifies essential competencies emphasized in innovative curricula, and maps conceptual and methodological gaps in prior research. This study applied a systematic literature review following the PRISMA 2020 guidelines. The researchers retrieved articles from Scopus databases covering publications from 2015 to 2024. The screening process reduced 145 initial records to 28 empirical studies that met inclusion criteria focusing on counselor education, curriculum innovation, and competency development while excluding conceptual and non-peer-reviewed sources. Thematic synthesis identified nine dominant competency themes, including multicultural competence, intrapersonal and interpersonal skills, wellness, spirituality, leadership, creativity, professional identity, and interprofessional collaboration. The analysis showed that experiential learning appeared as the most frequently implemented instructional approach, followed by cultural immersion, narrative supervision, and interprofessional training. Despite the breadth of identified competencies, existing studies demonstrate limited curricular integration and substantial methodological variation. This review highlights the need for holistic, evidence-based curriculum frameworks and directs future research toward developing integrative curriculum models and rigorously evaluating curriculum effectiveness